PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (PBV) PADA PT JAYA REAL PROPERTY TBK PERIODE 2013-2022 - Alda Dwi Juliana; Agus Supriatna (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the effect of profitability, as measured by return on equity (roe), and leverage, as measured by the debt to equity ratio (der), on company value, as measured by price book value (pbv), at pt jaya real property tbk during the 2013-2022 period. the method used is a quantitative research method with secondary data from the company's annual financial reports available on the indonesia stock exchange (bei). the results of the analysis show that profitability (roe) has no significant effect on company value (pbv), with a significant value of 0.701 > 0.05, and a calculated t value of 0.400 < t table 2.365. however, leverage (der) has a significant effect on company value (pbv), with a significant value of 0.001 <0.05, and a calculated t value of 10,605> t table 2.365. simultaneously profitability (roe) and leverage (der) have a significant effect on company value (pbv) with a significant value of 001<0.05 with f count of 168.916> f table 4.74. determination of r square (r2) is 98.0% while the remaining 2% is the influence of other factors that were not examined.